Clinical Outcomes of May–Thurner Syndrome in Pediatric Patients: A Single Institutional Experience - Warad, Deepti M.; Rao, Amulya Nageswara; Bjarnason, Haraldur; Rodriguez, Vilmarie (TH Open, 2020)
Introduction May–Thurner syndrome (MTS) is a vascular anatomic variant resulting in compression of the left common iliac vein by the right common iliac artery, affecting approximately 22% of the population. In adults, following acute deep vein thrombosis (DVT) of the iliofemoral veins, the incidence of postthrombotic syndrome (PTS) and recurrent DVT are high if treated with anticoagulation alone, warranting adjunctive treatment with thrombolysis and stent placement. However, there is paucity of literature documenting the course of treatment and associated outcomes in pediatric patients with MTS.Methods A retrospective chart review of pediatric patients (≤ 18 years of age) with radiologic confirmation of MTS with or without DVT evaluated and/or treated at our institution from January 1, 2005 through December 31, 2015 was conducted.Results Seventeen patients (4 male; 13 female) were identified. Median age was 15.4 years (range 8.8–17.1 years) with a median follow-up of 1.2 years (range 0.4–7.5 years). Thirteen (76.5%) patients presented with left lower extremity DVT. Management included catheter-directed thrombolysis (n = 5), systemic thrombolysis (n = 1), and mechanical thrombectomy (n = 1). Fifteen patients were treated with anticoagulation including two patients with endovascular stents without DVT. Median duration of anticoagulation was 6.3 months (range 3.2–18.7 months). Ten patients (59%) underwent stent placements.Complete and partial thrombus resolution was noted in six patients each and no resolution in one patient. Four patients had recurrence/progression of thrombus (n = 3 with stents) at a median time of 29 days (range 12–495 days). No bleeding complications were observed. Clinically documented or self-reported PTS was noted in 8 patients (62%).Conclusion There are no clear guidelines for MTS management in children and adolescents. In our cohort, thrombolysis, anticoagulation, or stent placements were not associated with bleeding risks, with recurrence/progression of DVT and signs and symptoms of PTS noted in 30 and 62%, respectively. Further studies are needed to determine a standardized treatment approach of the pediatric patient with MTS with or without thrombosis.
Keywords: May–Thurner syndrome; deep vein thrombosis; pediatric; children